Meningkatkan Hasil Belajar Siswa Kelas V Melalui Penerapan Media Pembelajaran Audio Visual Powtoon - Sukis, Sukis (Science and Education Journal (SICEDU), 2022)
This study aims to find out how to improve student learning outcomes through the application of audio visual powtoon learning media for fifth grade students at SDN Ngemplak II. This type of research is classroom action research. This research was conducted at SDN Ngemplak II on August 2 to August 30, 2022. The subjects of this study were the fifthgrade students of SDN Ngemplak II, totaling 16 people consisting of 10 boys and 6 girls. This research was carried out in collaboration between researchers, classroom teachers and student participation. This classroom action research was carried out in cycle II, where the first cycle consisted of two meetings. Based on the results of the study, it can be concluded that using audio visual powtoon media can improve student learning outcomes, this can be seen from the learning outcomes of class V students where from the initial ability (Pretest) students' learning outcomes are 41.67% with an average value 67.1 after the action in the first cycle, the percentage obtained reached 66.67% with an average value of 73.8, and in the second cycle increased to 91.67% with an average value of 82.9. The number of student activity scores in the first cycle is 3.3 (enough) and the second cycle is 4.1 (good).